EFFECT OF THICKNESS OF OVERLAYING CLAY LAYER OF LOWLAND REGION ON SENSITIVITY OF LATERAL DEFLECTION OF LONG PILES EMBEDDED IN NONHOMOGENEOUS SOIL - PART I: THEORETICAL FORMULATION - D. H. Hafez; B. B. Budkowska (International Association of Lowland Technology, 2006)
The importance of sensitivity analysis of soil-structure interaction system is embodied in two facts, that is, the soil is a nature-made material that affects the system’s performance and the sensitivity theory constitutes an inherent part of the behavior of the system. Moreover, the access to the supporting system is limited. Therefore, it is essential to have a reliable basis for the assessment of how changes of the parameters of the system affect its performance. The paper presents the study of sensitivity of laterally loaded piles using the distributed parameter sensitivity method. Other available sensitivity methods are briefly described in the paper. The theoretical formulation of the sensitivity of the lateral head deflection of piles embedded in non-homogeneous soil to changes in the design parameters is derived. The non-homogeneous soil consists of soft clay overlying sand and the design parameters are those that define the pile and the adjacent clay and sand. The formulation resulted in obtaining sensitivity operators that can show along the pile length where and how the change of each parameter affects the change of lateral pile-head deflection. The formulation provides the basis for studying the effect of the thickness of the overlying clay on the sensitivity results.